Quality of life in patients with vestibular Schwannoma - A literature review - Filho, Arthur Gustavo Gouveia Marques; Antoniou , André Kyriacos Menezes Haji; Vieira, Mariana Moraes; Sampaio, Brenno Santos; Moraes, Luzia Reis Rabelo de; Souza , Luana Thaynar Correia de; Messias, Yasmin Prado; Vieira, Gabriela Santana Reis; Fonseca , Pedro Carvalho; Melo , Maria Beatriz Meneses (Seven Editora, 2023)
Although Vestibular Schwannomas (SV) are benign tumors, they can cause symptoms such as hearing loss, tinnitus, balance disorders, etc. Such manifestations reduce the quality of life (QOL), in such a way that patients with VS report worse QOL than patients with chronic diseases or head and neck cancer. As VS is not a life-threatening disease if properly treated, most patients will live with their tumor, associated symptoms, and/or sequelae of therapy for long periods. DOI:https://doi.org/10.56238/devopinterscie-281